The Exploring Lecturers' Challenges in Implementing Flipped Learning in the Classroom - Pilu, Reski; Jabu, Baso; Iskandar, Iskandar; Upa, Rahmawati (Ethical Lingua: Journal of Language Teaching and Literature, 2025)
This qualitative study explores the challenges faced by lecturers in implementing flipped learning in classroom settings. Through in-depth interviews and observations, the research identifies key barriers such as student preparedness, technological issues, and resistance to new pedagogical approaches. The findings reveal that while some students engage actively when they come prepared, many others struggle to see the value in pre-class materials, which affects overall class dynamics. Furthermore, the study highlights the importance of collaboration among educators, as working with experienced colleagues can provide invaluable resources and strategies to mitigate these challenges. The insights gained from this research contribute to a deeper understanding of the complexities involved in adopting flipped learning and offer practical recommendations for enhancing student engagement and improving teaching practices in higher education.